2021
DOI: 10.1136/bmjopen-2020-044066
|View full text |Cite
|
Sign up to set email alerts
|

Baseline risk factor prevalence among adolescents aged 15–17 years old: findings from National Non-communicable Disease Monitoring Survey (NNMS) of India

Abstract: ObjectiveTo generate national estimates of key non-communicable disease (NCD) risk factors for adolescents (15–17 years) identified in the National NCD Monitoring Framework and, study the knowledge, attitudes and practices towards NCD risk behaviours among school-going adolescents.Design and settingA community-based, national, cross-sectional survey conducted during 2017–2018. The survey was coordinated by the Indian Council of Medical Research—National Centre for Disease Informatics and Research with 10 reput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 12 publications
(16 reference statements)
2
20
1
Order By: Relevance
“…A study conducted among 15–17 year old youth (n = 1531) in 27 states found that 25.2% of adolescents did not meet moderate-to-vigorous physical activity (MVPA) guidelines. 16 The survey-based data found that a higher proportion of urban residents were insufficiently physically active (38%), as well as girls (29.3%) in the sample. A total of 64.3% reported doing physical activity in schools and spent an average of 16.1 min per day.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…A study conducted among 15–17 year old youth (n = 1531) in 27 states found that 25.2% of adolescents did not meet moderate-to-vigorous physical activity (MVPA) guidelines. 16 The survey-based data found that a higher proportion of urban residents were insufficiently physically active (38%), as well as girls (29.3%) in the sample. A total of 64.3% reported doing physical activity in schools and spent an average of 16.1 min per day.…”
Section: Resultsmentioning
confidence: 90%
“…Overall Physical Activity refers to the proportion of children and adolescents meeting PA guidelines. 13 , 14 Evidence from 27 states in India (N = 3808 across urban and rural jurisdictions) was appraised to grade Overall Physical Activity , 15 , 16 , 17 , 18 as well as primary data from urban and rural children and adolescents aged 5–17 years (n = 1042).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed methodology of the survey has been published elsewhere. [20][21][22] The tools used for the study were adapted from the WHO-STEPwise approach to NCD risk factor surveillance (WHO-STEPS), 23 Integrated Disease Surveillance Project-NCD risk factor survey, 24 and WHO-Global Adult Tobacco Survey. 25 Questions on PA were derived from the WHO-Global Physical Activity Questionnaire.…”
Section: Sampling Design and Study Toolsmentioning
confidence: 99%
“…21,22 Considering Composition of time spent in PA by domain among adults (18-69 y) in India. PA indicates physical activity.…”
mentioning
confidence: 99%